Study on Physical Health Promotion of Teenagers based on Cognitive Neuropsychological Factors - Cai Jinming (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Physical health is a core component of the overall development of adolescents with practical significance for promoting and sustaining teenagers' physical health. This paper explores and studies the existing problems associated with adolescent physical health and designs a health promotion program based on numerical simulation. This is done through an intervention group and a control group of students’ sports variables intervention effect. A comprehensive and in-depth understanding of the implementation of students' physical health education provides impetus for the development of students' physical health education. On this basis, the primary focus is on the analysis of students' physical fitness. The study shows that some students from a few ethnic groups investigated the differences in physical fitness of some minority students according to the data obtained from the Physics research. The resulting data makes it possible to study the physical condition of students visually and intuitively. The results show that the main reasons for the decline of adolescents' physical fitness are social, school or family-related, and individual level `problems. The results of the analysis of covariance show that there are significant between-group effects on post-test Reasoning Test scores and attention allocation scores, and the experimental group has significantly higher post-test Reasoning Test scores and attention allocation scores than the control group; there are no significant between-group effects on behavioral performance scores of executive control, attention breadth, attention stability, and attention switching scores, and there are no significant differences between the experimental and control groups.